Strategi Pemasaran Digital Berbasis Influencer Lokal Dalam Menghadapi Perubahan Tren Konsumen Pada Bisnis Food & Beverage Di Bangka Belitung - Iin Kurnia; Yusnita Yusnita (Pusat Riset dan Inovasi Nasional, 2026)
This study explores the effectiveness of digital marketing strategies that utilize local influencers in responding to emerging consumer trends within the Food and Beverage (F&B) sector in Bangka Belitung. The research focuses on how local influencers affect consumer purchase decisions and which digital approaches are most relevant for businesses. Guided by Terence A. Shimp’s influencer marketing theory, the study employs a mixed-methods design combining surveys, in-depth interviews, and Focus Group Discussions (FGD) with business actors and local influencers. The findings indicate that local-influencer-based digital marketing is highly effective in building trust, strengthening consumer engagement, and enhancing brand awareness, particularly among Millennial and Gen Z audiences. The success of this strategy depends largely on the alignment between the influencer’s character and the business concept, as well as the authenticity and credibility of the content. Overall, the study highlights the strategic potential of local influencers in supporting the growth and competitiveness of F&B businesses in Bangka Belitung.